Fetal karyotyping in adolescent pregnancies: a population-based cohort study on outcomes of invasive prenatal testing - Staniczek, Jakub; Manasar-Dyrbuś, Maisa; Sodowska, Patrycja; Sodowski, Krzysztof; Włoch, Agata; Czuba, Bartosz; Cnota, Wojciech; Paul-Samojedny, Monika; Kania, Agnieszka; Sodowska, Henryka; Rybak-Krzyszkowska, Magda; Kondracka, Adrianna; et al. (Frontiers in Genetics, 2025)
BackgroundAdolescent pregnancies present unique challenges in prenatal diagnostics, yet data on the prevalence and types of chromosomal abnormalities in this population remain limited.ObjectiveThis study aimed to assess the prevalence and spectrum of chromosomal abnormalities and evaluate the effectiveness of invasive prenatal diagnostic procedures.MethodsA retrospective cohort study analyzed data from invasive prenatal diagnostic procedures (amniocentesis and transabdominal chorionic villus sampling) and fetal karyotyping in adolescent pregnancies, comparing them with data obtained from pregnancies in older women.ResultsAbnormal karyotype prevalence varied by age. Trisomies were least frequent in adolescents (5.9%) vs. women 20–34 (9.3%) and ≥35 years (12.1%). Turner syndrome was more common in adolescents (4.6%) than in women 20–34 (2.8%) or ≥35 years (0.1%). Adolescents had a higher risk of unspecified fetal sex (RR = 2.25, 95% CI: 1.16–4.35) and culture failure (RR = 4.32, 95% CI: 2.07–9.00). Ultrasound abnormalities were the main reason for invasive testing (86.3%, p < 0.001). More chorionic villus sampling procedures were needed per abnormal karyotype in adolescents (3.25) vs. women 20–34 (2.42) or ≥35 years (2.19), while fewer amniocenteses were required (6.68 vs. 7.37 and 8.44).ConclusionAdolescents show unique chromosomal abnormalities, underscoring the need for tailored prenatal counseling and diagnostics.